2002
DOI: 10.1038/sj.bjp.0704769
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M stimulates proliferation, induces collagen production and inhibits apoptosis of human lung fibroblasts

Abstract: 6JJ1 Oncostatin M (OSM), a member of the interleukin-6 (IL-6) cytokine family, acts on a variety of cells and elicits diversi®ed biological responses, suggesting potential roles in the regulation of cell survival, di erentiation and proliferation. 2 We have examined the e ect of OSM on the regulation of human lung ®broblast proliferation, collagen production and spontaneous apoptosis. The proliferative e ects of OSM (0.5 ± 100 ng ml 71 ) were assessed using a MTS assay as well as [ 3 H]-thymidine incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 42 publications
6
74
0
Order By: Relevance
“…OSM has been reported to promote proliferation of mesenchymal cells 25,26 and thus may be important for the bone marrow alterations associated with systemic mastocytosis. Therefore, we next wished to determine whether OSM derived from KIT D816V ϩ neoplastic cells can stimulate growth of mesenchymal cells.…”
Section: Osm Derived From Neoplastic Mast Cells Promotes Growth Of MImentioning
confidence: 99%
See 1 more Smart Citation
“…OSM has been reported to promote proliferation of mesenchymal cells 25,26 and thus may be important for the bone marrow alterations associated with systemic mastocytosis. Therefore, we next wished to determine whether OSM derived from KIT D816V ϩ neoplastic cells can stimulate growth of mesenchymal cells.…”
Section: Osm Derived From Neoplastic Mast Cells Promotes Growth Of MImentioning
confidence: 99%
“…24 Later, OSM was shown to act as a growth factor for mesenchymal cells, including endothelial cells, fibroblasts, and osteoblasts. [25][26][27][28] Recently, OSM has been implicated as an important cytokine in hematopoiesis. Transplantation experiments with OSM-deficient mice have shown that OSM stimulates stromal cells as well as hematopoietic progenitors and is required for the generation and maintenance of a proper microenvironment in the bone marrow.…”
mentioning
confidence: 99%
“…The gene with the greatest increase in expression in the array analyses was oncostatin M ( Figure 3D). Oncostatin M, a growth factor produced by activated T cells (63), stimulates collagen production and fibroblast proliferation (64). To confirm the increased expression of the oncostatin M gene, oncostatin M protein was measured in BAL fluid from patients with and without lung inflammation as well as from healthy controls.…”
Section: Cd8ϩ T Cells In Scleroderma Lung Disease 2267mentioning
confidence: 99%
“…OSM is a multi-functional cytokine secreted by monocytes and T cells. It is pro-angiogenic [19], modulates growth and differentiation in normal fibroblasts [20] and some malignant cells [21], and stimulates production of acute-phase response proteins in hepatocytes [22]. OSM is secreted on LPS stimulation of mononuclear and dendritic cells, [23] both of which are important cellular effectors of a protective immune response to Mtb.…”
Section: Introductionmentioning
confidence: 99%